2014
DOI: 10.3904/kjim.2014.29.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of antioxidant capacity using the biological antioxidant potential test and its role as a predictive marker of metabolic syndrome

Abstract: Background/AimsOxidative stress increases the risk of cardiovascular complications of metabolic syndrome (MetS). This study was conducted to examine the difference in antioxidant capacity according to the presence of MetS, and to characterize the association between antioxidant capacity and MetS-related factors.MethodsWe used the biological antioxidant potential (BAP) test to estimate antioxidant capacity. The BAP test has recently been used as an indicator of antioxidant capacity. We measured BAP levels in 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
2
19
1
Order By: Relevance
“…d-ROM levels are the total levels of peroxidized metabolites, whereas BAP reflects serum antioxidant capacity. These markers are known to correlate with the development of metabolic syndrome, cardiovascular disease, and hepatocellular carcinoma (37)(38)(39). In this study, a significant decrease in d-ROM was observed in the 0.20% LRP group, and a significant increase in BAP was observed in the 0.05% LRP and 0.20% LRP groups.…”
Section: Discussionsupporting
confidence: 50%
“…d-ROM levels are the total levels of peroxidized metabolites, whereas BAP reflects serum antioxidant capacity. These markers are known to correlate with the development of metabolic syndrome, cardiovascular disease, and hepatocellular carcinoma (37)(38)(39). In this study, a significant decrease in d-ROM was observed in the 0.20% LRP group, and a significant increase in BAP was observed in the 0.05% LRP and 0.20% LRP groups.…”
Section: Discussionsupporting
confidence: 50%
“…Based on our previous experience, in order to evaluate the OS we chose d‐ROMs test and BAP test as suitable tests to measure total oxidant and total antioxidant capacity, respectively, on blood serum samples . This choice was dictated by the well‐established analytical performances of these tests that allow them (i) to accurately measure the OS level ex vivo either in subject at risk for OS (eg cigarette smokers and alcohol drinkers) or in patients suffering from OS‐related diseases, including cardiovascular and inflammatory diseases, cancer and onco‐haematological disorders; (ii) to be sensitive to changes occurring after specific treatments, antioxidant supplementation and radio‐ or chemotherapy; (iii) to anticipate the progression of OS‐related diseases during a systematic monitoring; and (iv) to be minimally invasive, highly compliant, fast, with an optimal cost/benefit ratio . Both d‐ROMs test and BAP test have been validated by the gold standard methods to assess redox balance ex vivo (ie the electron spin magnetic resonance spectrometry), and their reference values in large cohorts of general population are well established .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the levels of oxidative stress markers in the blood are increased in patients with cataract (5). Oxidative stress in the blood causes cataract and other life-style related diseases due to an imbalance in the ratio of ROS and antioxidants (6). Superoxide dismutase (SOD) is a reaction enzyme that catalyzes the dismutation of superoxide into oxygen and hydrogen peroxide and maintains the body redox state in coordination with CAT (7).…”
Section: Introductionmentioning
confidence: 99%